GAYA BAHASA DALAM KONTEN TIKTOK GENERASI Z: KAJIAN STILISTIKA TERHADAP DIKSI, MAJAS, DAN CITRAAN - Hendri Hendri; Siti Khaeranil Bariah (Lembaga Berugak Baca, 2026)
This study aims to describe the language style employed by Generation Z in TikTok content through a stylistic analysis focusing on diction, figurative language, and imagery. The research adopts a qualitative approach using a descriptive method. The data consist of utterances, narrations, and captions found in TikTok content produced by Generation Z. Data were collected through observation, note-taking, and documentation techniques and were analyzed using descriptive qualitative analysis. The findings reveal that the diction used in TikTok content is predominantly characterized by colloquial language, slang, abbreviations, and popular expressions, reflecting the distinctive features of Generation Z's digital communication. In terms of figurative language, the study identifies the use of metaphor, hyperbole, personification, simile, irony, and satire, which function to reinforce messages, create humor, express emotions, and convey social criticism. Meanwhile, the imagery found in the data includes visual, auditory, kinesthetic, tactile, and emotional imagery, all of which contribute to stimulating the audience's imagination while producing aesthetic and emotional effects. The study concludes that diction, figurative language, and imagery are essential stylistic elements that shape the linguistic characteristics of Generation Z on TikTok. These three elements function not only as means of communication but also as instruments of self-expression, social identity construction, and strategies for enhancing content appeal within the digital environment.